The role of NK family receptor interactions with HLA-B27 in Ankylosing Spondylitis pathogenesis - Giles, J (2011)
Possession of the Major Histocompatibility Complex (MHC) allele, HLA-B27 (B27), strongly predisposes to the development of spondyloarthritis. Furthermore, B27 exists as polymorphic variants, with some subtypes (such as B*2705) being more strongly associated with disease than others (B*2709). The immunological function of MHC molecules is to present peptides in a heterotrimeric complex with beta-2-microglobulin (β2m); however, B27 has also been observed to form non-classical (β₂m –free) homodimers at the cell surface. It has been suggested that there may be a pathogenic role for cell surface B27 homodimer interactions with Natural Killer (NK) cell receptors, such as Leukocyte Immunoglobulin like Receptors (LILRs). In this thesis I characterise these interactions and investigate molecular differences between two B27 subtypes. Here I show that the B*2705 subtype forms homodimers more readily than the B*2709 subtype, but once formed, B27 homodimers of the 2 different subtypes exhibit comparable binding specificities and affinities to the NK receptors. On the other hand, I show significant differences in the binding specificities and affinities of these receptors to B27 homodimers and heterotrimers. LILRB1 does not bind B27 homodimers, but does bind B27 heterotrimers. LILRB2 binds B27 heterotrimers with a KD of 22μM, whereas LILRB2 binds B27 homodimers more strongly with a KD of 2.5μM. In addition to these main findings, I have characterised the specificity and affinity of candidate B27 homodimer-specific antibodies. I have performed epitope-mapping experiments and developed a model for binding to the B27 homodimer. Finally, I have identified crystallisation conditions for the B27 homodimer in complex with a Fab, allowing for X-ray crystallography studies. In this thesis, I have characterised for the first time the molecular interactions of the B27 homodimer with NK cell ligands and show that they are different from those with the B27 heterotrimer. This work supports a hypothesis of B27 homodimer induced pathology involving NK receptors.